Pathogenesis of the Limb Manifestations and Exercise Limitations in Peripheral Artery Disease. Issue 9 (24th April 2015) - Hiatt, William R.; Armstrong, Ehrin J.; Larson, Christopher J.; Brass, Eric P.
<x xml:space="preserve">Abstract</x> Patients with peripheral artery disease have a marked reduction in exercise performance and daily ambulatory activity irrespective of their limb symptoms of classic or atypical claudication. This review will evaluate the multiple pathophysiologic mechanisms underlying the exercise impairment in peripheral artery disease based on an evaluation of the current literature and research performed by the authors. Peripheral artery disease results in atherosclerotic obstructions in the major conduit arteries supplying the lower extremities. This arterial disease process impairs the supply of oxygen and metabolic substrates needed to match the metabolic demand generated by active skeletal muscle during walking exercise. However, the hemodynamic impairment associated with the occlusive disease process does not fully account for the reduced exercise impairment, indicating that additional pathophysiologic mechanisms contribute to the limb manifestations. These mechanisms include a cascade of pathophysiological responses during exercise-induced ischemia and reperfusion at rest that are associated with endothelial dysfunction, oxidant stress, inflammation, and muscle metabolic abnormalities that provide opportunities for targeted therapeutic interventions to address the complex pathophysiology of the exercise impairment in peripheral artery disease.